Gender and violence against political actors - Bjarnegård, Elin; Zetterberg, Pär (Temple University Press, 2023)
"This edited volume brings together U.S. and European scholars within political science, comparative politics, international relations, and other related disciplines and practitioner fields to offer theoretical and methodological perspectives on gender and political violence and to encourage conversation across subfields and disciplines on the topic"--